Türk seramik kaplama malzemeleri sektörünün rekabet analizi ve uluslararası bir strateji önerisi - Baş, Abdurrahman (My University, 1999)
Competitiveness Analysis Of And A Global Strategy Proposal For The Turkish Ceramic Tiles Industry ABSTRACT In this study, the strategic analysis framework that is generally used at the company level tried to be applied to the industry level. In that respect, the strategy formulation process is also attempted to be performed at that level. The new industry level analysis framework mostly derived from company level analysis with some minor but deliberate modifications. In line with current arguments in the literature, the new framework is called competitiveness analysis. The competitiveness analysis framework narrows its focus from global trends through inner dynamics. It especially pays attention to competitive forces. As an application example, Turkish ceramic tile industry is selected for its global competitive potential. For the analysis, related information materials and industry specialists are consulted. As the study extends to suggest a national strategy for the industry, some social and political aspects reviewed by an interdisciplinary approach. For the strategy proposal, an eclectical but a unique approach is generated and a sound strategy formulated. It is concluded that, a new competitiveness analysis framework and a strategy formulation at the industry level is not only possible but also necessary in our world of increasing trade and competition. Türk Seramik Kaplama Malzemeleri Sektörünün Rekabet Analizi Ve Uluslararası Bir Strateji Önerisi

Bu çalışmada, işletmelerin stratejilerini belirleme sürecinde başvurdukları sektör analizi çerçevesinin, işletme düzeyinden sektörel düzeye taşınması ve buna paralel olarak, strateji formülasyonunun yine sektörel düzeyde gerçekleştirilmesi konu edinilmiştir. Sektörel analiz çerçevesini belirlerken, stratejik yönetim literatüründe var olan işletmelerin stratejik analizi çerçevesinden yararlanılmış, strateji tanımının son yıllardaki evrimi dikkate alınarak oluşturulan çerçeveye rekabet analizi çerçevesi denilmiştir. Rekabet analizi çerçevesi, en dış çevreden iç yapıya doğru analiz odağını daraltmakta, rekabet avantajı sağlayan unsurların derinlemesine incelenmesini ön plana almaktadır. Örnek sektör olarak, Türkiye'nin küresel pazarda umutlu olduğu seramik kaplama malzemel
Keywords: REKABET